2003
DOI: 10.1897/02-340
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pore‐water ammonia on in situ survival and growth of juvenile mussels (;Lampsilis cardium); in the St. Croix Riverway, Wisconsin, USA

Abstract: We conducted a series of in situ tests to evaluate the effects of pore-water ammonia on juvenile Lampsilis cardium in the St. Croix River (WI, USA). Threats to this river and its associated unionid fauna have accelerated in recent years because of its proximity to Minneapolis-St. Paul, Minnesota, USA. In 2000, caged juveniles were exposed to sediments and overlying water at 12 sites for 10 d. Survival and growth of juveniles was significantly different between sediment (mean, 47%) and water column (mean, 86%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
3
23
0
Order By: Relevance
“…In the sediments tests, growth rate declined an order of magnitude between the controls and the highest ammonia treatment; in the water-only tests, juvenile mussels grew slowly, regardless of treatment. Likewise, growth rates of juvenile L. cardium ranged from 3 to 20 m/d after a 4-d in situ deployment in the St. Croix River (MN and WI, USA) [34]. The considerable growth in the controls in the sediment tests suggests that juvenile mussels received substantial benefit from the presence of sediment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the sediments tests, growth rate declined an order of magnitude between the controls and the highest ammonia treatment; in the water-only tests, juvenile mussels grew slowly, regardless of treatment. Likewise, growth rates of juvenile L. cardium ranged from 3 to 20 m/d after a 4-d in situ deployment in the St. Croix River (MN and WI, USA) [34]. The considerable growth in the controls in the sediment tests suggests that juvenile mussels received substantial benefit from the presence of sediment.…”
Section: Discussionmentioning
confidence: 96%
“…Second, studies should examine the effects of pH on ammonia toxicity. However, in a field study, TAN concentrations varied from Ͻ1 to 2 mg/L in pore water from the relatively uncontaminated St. Croix River; yet, survival and growth of in situ-deployed juvenile mussels were generally unrelated to ammonia concentrations [34]. Toxicol.…”
Section: Discussionmentioning
confidence: 98%
“…Increased growth of mussels in low and intermediate treatment concentrations partially may be explained by the additional carbon or nitrogen from test compounds available for microorganisms, which in turn could provide a supplemental food source for the mussels [32,33]. Interestingly, an inverted Ushaped concentration-response curve, in contrast to a traditional linear toxicity response curve, was evident for growth of mussels exposed to Roundup, technical-grade glyphosate IPA salt, and Aqua Star; however, the difference in growth of treatments compared to controls was not statistically significant for any of these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…While there are concerns that ammonia toxicity contributes to large-scale declines in freshwater invertebrates (e.g., Sparks & Sandusky, 1981;Wilson et al, 1995), we found no published evidence that natural conditions in the UMR lead to toxic levels of unionized ammonia (NH 3 ). The only in situ study we are aware of that evaluated ammonia toxicity on a highly susceptible organism (juvenile unionid mussels) found no evidence of elevated mortality or decreased growth in a wide range (range: 7.9-187 lg l -1 NH 3 -N) of porewater ammonia concentrations (Bartsch et al, 2003). In fact, the highest proportion of live juveniles was found at the highest NH 3 concentrations, and growth rates were positively related to NH 3 concentrations (Bartsch et al, 2003, Fig .…”
Section: In Unenriched Waters Concentrations Of Nh 3 or Nhmentioning
confidence: 95%